The evolution of heliophysics: Complexity, community, and open science - McGranaghan, Ryan M. (Frontiers in Astronomy and Space Sciences, 2022)
Responding to the grand challenges that confront the Earth and Space Sciences requires an embrace of methods from the field of complexity and systems science that can adapt our thinking and our science to be more inter- and cross-disciplinary and enable broader connection across individuals, teams, communities, and sciences. Culturally, as scientifically, broader disciplinary approaches are imperative. The cultural challenge is the disconnect that exists between groups. These disconnects preclude plurality in discussions, harm creativity and innovation, and give rise to a palpable malaise, especially at the early career stage. Together, the scientific and cultural grand challenges we describe point to a need for a new set of literacies and curriculum that the advent of open science supports--increased cross-disciplinarity, team science that generates community connections, plurality and inclusion in our science and in how we connect.